Sains dan Islam: Integrasi islam dalam Pembelajaran Sains tentang Reproduksi Manusia di Universitas Islam Negeri Sultan Syarif Kasim Riau - Fauzan, Mohd; Hitami, Munzir; Yusuf, Kadar M (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The purpose of this study was to analyze Islamic integration in learning science about human reproduction at Sultan Syarif Kasim Riau State Islamic University. This study uses a qualitative descriptive method through field research, using the integration of science and Islam in human reproduction material. The results and discussion of this study indicate that the learning process that has been implemented has not fully implemented the integration of science and Islam in learning human reproduction. This can be seen in the learning tools that each sub-discussion has not been fully integrated with the Koran, and the learning process has not been fully refined with the uluhiyah messages contained in the Koran. This study recommends that learning in Islamic tertiary institutions carry out the integration of science and Islam.